PENERAPAN MODEL PEMBELAJARAN COOPERATIF TYPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA TENTANG TEKS INTERAKSI INTERPERSONAL LISAN DAN TULIS PADA MATA PELAJARAN BAHASA INGGRIS - Neti Anniati (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
APPLICATION OF THE JIGSAW COOPERATIVE LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES ABOUT INTERPERSONAL INTERPERSONAL INTERACTION TEXTS AND WRITING IN ENGLISH SUBJECTSThis research is a Classroom Action Research by providing action on research subjects in two learning cycles. This study aims to determine the application of the Type Jigsaw cooperative learning model can improve student learning outcomes in English subjects about oral and written interpersonal interaction texts in Class IX Junior High School (SMP Negeri 5 Kota Bogor)  Odd Semester 2019/2020 Academic Year. Another goal is to describe the process of improving student learning outcomes about oral and written interpersonal interaction texts in English subjects after using the Jigsaw Type Cooperative Learning Model. To measure the magnitude of the increase in student learning outcomes about oral and written interpersonal interaction texts in English subjects after using the Jigsaw Type Cooperative Learning Model in. The results of this study indicate that before using the cooperative learning model Type Jigsaw, the learning outcomes of students only reached an average value of 66.32 then an increase occurred after using the Make A Match cooperative learning model to 73.53 in cycle 1 and 81.03 in cycle. 2. By using the cooperative learning model Type Jigsaw can be a fun variation of learning for students so that it is proven to improve student learning outcomes in Class IX semester 1  Junior High School (SMP Negeri 5 Kota Bogor).